Clinical profile and surgical outcomes of children presenting with teratology of Fallot - Chinawa, Josephat M; Vijay, Agarwal; Gaikwad, Sarang; Trivedi, Bhadra; Chukwu, Bartholomew (Journal of Cardiology and Cardiovascular Medicine, 2020)
Background: Tetralogy of Fallot (TOF) is a very common cyanotic congenital heart disease presenting early at birth with various degrees of cyanosis. If left uncorrected surgically, can lead to death. Objectives: This study is aimed at determining pattern and surgical outcome of children with teratology of Fallot in a budding health facility in India over a year period. Result: A total of 51 children were diagnosed of TOF over the period, of which 66.7% were males with mean age of 48.14 ± 45.36 months. The surgical outcome showed only 3.9% mortality. The death was among children >1 to 5 years. The mean number of days in intensive care unit (ICU) was 5.8 ± 11.2 days. 82.4% of the patients were off-pump post-operatively, compared to 17.6% with re-pump. Among those who had re-pump, 77.8% were males and among those without re-pump, 64.3% were likewise males (χ2 = 0.6, p = 0.41). About 92.2% (47/51) of patients had pulmonary regurgitation post-op, ranging from mild to moderate regurgitation. 51.1% of the regurgitations were mild while 25.5% and 23.4% were moderate and severe regurgitations respectively. Post-operative VSD was detected in 51% (26/51) of the patients. The post-op right ventricular pressure (RVOT) was significantly lower than that of pre-op pressure, 10.8 ± 1.5 mmHg vs. 31.7 ± 4.5 mmHg (pair t test = 8.7, p < 0.001). Conclusion: Timely surgical repair is crucial in alleviating several morbidity and mortality associated with teratology of fallot. Pulmonary regurgitation is a very common sequel after surgery and can result in death.